Smartphone-based thermal imaging for pedicled skin flaps: a pilot study toward objective perfusion assessment in facial, head, and neck reconstruction - Fiedler, Lukas Sebastian; Meyer, Tobias; Lippert, Burkard M.; Adrian, Lukas (European archives of oto-rhino-laryngology and head & neck, 2024)
This study aims to develop a practical algorithm for utilizing smartphone-based thermal imaging (SBTI) in the perioperative setting and to establish a standardized evaluation method for objectively assessing SBTI images for cutaneous perfusion of pedicled flaps in the face, head, and neck.
Gesehen am 09.04.2025